Development and Evaluation of Ready-to-use Multiplex PCR Assays for the Detection of Major foodborne Pathogens - SHYLAJA RAMLAL; SOWMYA NAGARAJ; BATRA HARSHVARDHAN (International Journal of Pharma and Bio Sciences, 2018)
Foodborne diseases have emerged as a growing public health concern and economic burden leading to high morbidity and mortality worldwide. Oftentimes, foodborne outbreaks are due to the combined effect of multiple pathogens rather than a single organism. In this context, the present work was intended to develop and evaluate ready-to-use multiplex PCR (mPCR) assays for the detection of major foodborne pathogens. Various Gram positive and Gram negative bacteria which are frequently associated with foodborne illness were enlisted based on reported studies. Two mPCR assays were developed, each for the detection of listed Gram positive and Gram negative foodborne pathogens using specific gene targets. Though various multiplex PCR methods are accessible for the same, the use of these techniques for routine/regular diagnosis is restricted for number of reasons. Improvement of these traditional methods enables their feasibility and field application. To achieve the same, the master mixes of developed mPCR formats were subjected to lyophilization with a suitable lyoprotectant and storage stability studies were performed to assess the shelf life of both formats. The sensitivity as well as specificity of the assay formats was also examined. The shelf-life of both the lyophilized formulations was found to be six months at 4°C and 1.5 months at 280C – 300C temperature. The stability at ambient temperature enabled storage and transportation of these formulations without cold-chain requirement. In addition to user-friendly format, two assays were sensitive to detect 103 CFU/ml. The formats were also able to amplify target genes directly from food samples when tested. In the present study, a combination of major and multiple pathogens merely in two formats were made which would find their appropriate application during epidemiologic studies of foodborne outbreaks.